PERBANDINGAN KINERJA PERBANKAN INDONESIA DAN THAILAND. APAKAH ADA PERBEDAAN? - Yunita Ikasari Ratna Putri; Yuniorita Indah Handayani Indah Handayani (UNEJ e-Proceeding)
This study aims to compare bank performance of Indonesia banks and Thailand banks by using RGEC (Risk Profile, Good Corporate Governance, Earning, and Capital). The data that used is financial statements during 2010 to 2014. The sample method used in this study is purposive sampling. The whole samples are consist of 6 banks in Indonesia and 6 banks in Thailand. The descriptive test used to know mean, min, and max value each ratio in Indonesia and Thailand banks. Kolmogorov-smirnov test is used to test the normality of data distribution. Moreover, the hypothesis examination is used multivariat analysis of variance (MANOVA). The result showed that Indonesia banks better than Thailand banks for NPL, IRR, ROA, ROE, NIM, BOPO and CAR. Whereas, Thailand banks better than Indonesia banks in LDR and GCG. Simultaneously testing performed on RGEC indicators show that there are different between Indonesia banks and Thailand banks.